2022
DOI: 10.1021/jacs.2c06495
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Binding Site Interactions and Selectivity Principles in the α3β4 Nicotinic Acetylcholine Receptor

Abstract: Nicotinic acetylcholine receptors (nAChRs) play an important role in neurotransmission and are also involved in addiction and several disease states. There is significant interest in therapeutic targeting of nAChRs; however, achieving selectivity for one subtype over others has been a longstanding challenge, given the close structural similarities across the family. Here, we characterize binding interactions in the α3β4 nAChR subtype via structure−function studies involving noncanonical amino acid mutagenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Single-site mutagenesis by Knox et al revealed two amino acids to be particularly important for dictating this subtype selectivity. They found mutating Leu121 in β4 to phenylalanine present in β2 led to a 3-fold loss in potency, likely due to steric clash between the bromine atom and the large phenylalanine side chain . Decreasing the steric bulk in the binding site by mutating Ile113 to the smaller valine found in β2 also led to a decrease in potency, indicating that AT-1001 forms important hydrophobic interactions with the complementary face of the binding site.…”
Section: Azabicyclic Partial Agonistsmentioning
confidence: 99%
See 3 more Smart Citations
“…Single-site mutagenesis by Knox et al revealed two amino acids to be particularly important for dictating this subtype selectivity. They found mutating Leu121 in β4 to phenylalanine present in β2 led to a 3-fold loss in potency, likely due to steric clash between the bromine atom and the large phenylalanine side chain . Decreasing the steric bulk in the binding site by mutating Ile113 to the smaller valine found in β2 also led to a decrease in potency, indicating that AT-1001 forms important hydrophobic interactions with the complementary face of the binding site.…”
Section: Azabicyclic Partial Agonistsmentioning
confidence: 99%
“…These approaches, of course, require a clearly defined binding site. And while computational studies have been used to propose binding sites for α3β4 ligands, experimental evidence from mutated receptors and the incorporation of non-natural amino acids has proven considerably more useful in defining the ligand–receptor interactions that dictate ligand binding . In addition to developing the existing classes of α3β4 nAChR inhibitors, it is also important to continue to identify and explore new chemotypes that target these receptors.…”
Section: Summary and Outlook For α3β4 Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…endogenous neurotransmitter ACh and the smoking cessation drug cytisine. They examined the impact of selective cytosine derivatives on the ligand structure, concluding that certain nicotinic acetylcholine receptor (nAChR) targeted ligands can be availed to improve the design of advanced therapies [47].…”
Section: Medical Uses For the Cation-π Interactionmentioning
confidence: 99%